Long Term Hippocampal and Cortical Changes Induced by Maternal Deprivation and Neonatal Leptin Treatment in Male and Female Rats - Mela, Virginia; Díaz, Francisca; Borcel, Erika; Argente, Jesús; Chowen, Julie A.; Viveros, Maria-Paz (PLOS ONE, 2015)
Maternal deprivation (MD) during neonatal life has diverse long-term behavioral effects and alters the development of the hippocampus and frontal cortex, with several of these effects being sexually dimorphic. MD animals show a marked reduction in their circulating leptin levels, not only during the MD period, but also several days later (PND 13). A neonatal leptin surge occurs in rodents (beginning around PND 5 and peaking between PND 9 and 10) that has an important neurotrophic role. We hypothesized that the deficient neonatal leptin signaling of MD rats could be involved in the altered development of their hippocampus and frontal cortex. Accordingly, a neonatal leptin treatment in MD rats would at least in part counteract their neurobehavioural alterations. MD was carried out in Wistar rats for 24 h on PND 9. Male and female MD and control rats were treated from PND 9 to 13 with rat leptin (3 mg/kg/day sc) or vehicle. In adulthood, the animals were submitted to the open field, novel object memory test and the elevated plus maze test of anxiety. Neuronal and glial population markers, components of the glutamatergic and cannabinoid systems and diverse synaptic plasticity markers were evaluated by PCR and/or western blotting. Main results include: 1) In some of the parameters analyzed, neonatal leptin treatment reversed the effects of MD (eg., mRNA expression of hippocampal IGF1 and protein expression of GFAP and vimentin) partially confirming our hypothesis; 2) The neonatal leptin treatment, per se, exerted a number of behavioral (increased anxiety) and neural effects (eg., expression of the following proteins: NG2, NeuN, PSD95, NCAM, synaptophysin). Most of these effects were sex dependent. An adequate neonatal leptin level (avoiding excess and deficiency) appears to be necessary for its correct neuro-programing effect.